FAKTOR RISIKO PADA BALITA DENGAN BERAT BADAN DIBAWAH GARIS MERAH (BGM) DI WILAYAH KERJA PUSKESMAS HALMAHERA - Chintya Dewi Prastica Putri; Syamsulhuda Budi Mustofa; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Children with body weight under the red line (BGM) is an indication of malnutrition. The indicator of BGM is body weight based on age and can be known through graphs on KMS when weighing at the posyandu. Based on the results of the 2018 Riskesdas, the national underweight figure is 17.7% while the figure has not reached the 2019 RPJMN target. In 2017, Central Java has a toddler with malnutrition (body weight based on age) at 14% which increased from 2016 by 13.8%. Meanwhile in 2017, Puskesmas Halmahera get in top three with the highest of children with BGM at Semarang city. The purpose of this research was to determine risk factors for toddlers with body weight under the red line (BGM). This research used a case-control study with 58 respondents (29 case samples and 29 control samples). In this study, showed that history of a toddler’s diet consisting at low levels of energy sufficiency (51.7%), carbohydrates adequancy (50%), protein adequancy (50%), fat adequancy (36.2%), and poor environmental sanitation (43.1%). The results of the bivariate analysis (using chi-square test) there is relationship between toddler eating patterns (p-value 0,000) and environmental sanitation (p-value 0.001) with BGM status. So, toddlers who has a sufficient level of energy in category insufficient have a risk of 378 time experiencing BGM status.